Measurement of the inclusive isolated prompt photons cross section in pp collisions at $\sqrt{s}=7$ TeV with the ATLAS detector using 4.6 fb$^{−1}$ - ATLAS collaboration (2916 authors) (2014)
A measurement of the cross section for the production of isolated prompt photons in pp collisions at a center-of-mass energy $\sqrt{s}$ = 7 TeV is presented. The results are based on an integrated luminosity of 4.6 fb$^{-1}$ collected with the ATLAS detector at the LHC. The cross section is measured as a function of photon pseudorapidity $η^γ$ and transverse energy $E_T^γ$ in the kinematic range 100 < $E_T^γ$ < 1000 GeV and in the regions |$η^γ$| < 1.37 and 1.52 < |$η^γ$| < 2.37. The results are compared to leading-order parton-shower Monte Carlo models and next-to-leading order perturbative QCD calculations. Next to-leading-order perturbative QCD calculations agree well with the measured cross sections as a function of $E_T^γ$ and $η^γ$.